Digital Transformation in Islamic Banking: Examining User Adoption of BYOND BSI in Indonesia - Defrangga Piyu Pramudita; Rahmadani Aidil Fitrocahya; Mochamad Fuad Marzuki; Titis Miranti; Tiara Juliana Jaya (Journal of Finance and Islamic Banking, 2025)
Purpose: This study investigates the effects of perceived ease of use, perceived enjoyment, e service quality, and technostress on the decision to use the BYOND BSI super app within the digital transformation of Islamic banking in Indonesia, focusing on Islamic university students in the Malang Raya region. Method: A quantitative approach was applied using a structured questionnaire administered to 100 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling through SmartPLS 3.0 to assess the influence of digital factors on user adoption. Result: The findings show that perceived ease of use and technostress significantly affect the decision to use BYOND BSI, while e service quality has a moderate effect and perceived enjoyment is not significant. These results suggest that adoption behavior is primarily driven by functional convenience and technological pressure rather than hedonic motivation. Implication: The study extends the Technology Acceptance Model by incorporating technostress in the context of Islamic digital banking and highlights the need for simple system design reliable services and improved digital literacy to reduce user stress. Originality: This study contributes to Islamic fintech literature by empirically integrating technostress into the TAM framework and explaining user adoption behavior in Indonesia.